The Understanding of Human Rights in the Neo-Eurasianist Doctrine - Joachim Diec (Ksiegarnia Akademicka Publishing, 2021)
Neo-Eurasianism as a political doctrine is a descendant of the Eurasianist thought in the interwar period and L.N. Gumilev’s ethnological speculations during the Soviet era. Similarly to the oldest generation, Neo-Eurasianists, respond to the trauma of the lost empire in their thought: denying the leading position of the victorious competitor, they also deny the Western understanding of human rights. The polemic is conducted by a group of Russian visionaries, such as A. Panarin, A. Dugin, V. Korovin, as well as by much more pragmatic Kazakh theoreticians of law led by Z. Busurmanov. The Neo-Eurasianist narrative generally rejects the Lockean absolutization of inalienable individual’s rights and emphasizes the communitarian aspect instead. Russian Neo-Eurasianists blame the Western ideologists for treating human rights as a diplomatic weapon against foreign independent powers and try to present the liberal concept as a speculative idea. However, contrary to the Russian tradition, the idea of individual rights is not rejected in the Kazakh legal theory; it is presented in the light of a necessity to protect the right to cultivate one’s identity in the realities of a multiethnic state.